Future of Blockchain - Sadiku, Matthew N. O.; Chukwu, Uwakwe C.; Sadiku, Janet O. (Research Parks Publishers, 2023)
Blockchain is a decentralized system that keeps track of distributed data and provides encrypted transaction tracking. It has attracted attention with its unique characteristics, such as irrevocability and security. It will be a part of our everyday life. The future of blockchain will be determined by how effectively blockchain integrates with advanced technologies, such as artificial intelligence (AI), Internet of things (IoT), and 5G networking. This paper attempts to predict the future of blockchain technology.